225k views
2 votes
If f(x) = 7x^2 - 3x +1 and g(x) = 3x - 2, find the following by matching.

1. g(0)
2. g(1)
3. f(1)
4. f(-2)

User Dapa
by
5.7k points

1 Answer

3 votes

f(x) = 7x² - 3x + 1

g(x) = 3x - 2


1. g(0) This means that x is 0, so you can plug in 0 for x in the equation:

g(x) = 3x - 2

g(0) = 3(0) - 2

g(0) = -2


2. g(1) x is 1

g(x) = 3x - 2

g(1) = 3(1) - 2

g(1) = 3 - 2

g(1) = 1


3. f(1) x is 1

f(x) = 7x²- 3x + 1

f(1) = 7(1)² - 3(1) + 1

f(1) = 7 - 3 + 1

f(1) = 5


4. f(x) = 7x²- 3x + 1

f(-2) = 7(-2)²- 3(-2) + 1

f(-2) = 7(4) + 6 + 1

f(-2) = 28 + 7

f(-2) = 35

User Sean Cox
by
6.9k points